2019
DOI: 10.1016/j.jaci.2018.09.028
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroplastic changes in the olfactory bulb associated with nasal inflammation in mice

Abstract: Background: Rhinitis and rhinosinusitis are olfactory disorders caused by inflammation of the nasal passage and paranasal sinuses. Although patients with chronic rhinosinusitis have smaller olfactory bulbs (OBs), there is limited knowledge regarding the influence of chronic nasal inflammation on OB neurons. Objective: Repeated intranasal administration of LPS that induced persistent nasal inflammation in mice caused a loss of olfactory sensory neurons (OSNs) and gliosis and synaptic loss in the OBs within 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 66 publications
(84 reference statements)
5
56
0
Order By: Relevance
“…15 In animal models, instilling LPS into the nasal cavity of rats or mice can induce not only acute sinusitis but also the development of CRSwNP and olfactory dysfunction. 13,19,20 These findings further confirmed that noninfectious inflammatory factors were involved in the occurrence and development of inflammatory diseases. Although previous studies have shown that a certain amount of G − bacteria are present in CRSwNP, the expression and distribution of LPS in CRSwNP have not been investigated.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…15 In animal models, instilling LPS into the nasal cavity of rats or mice can induce not only acute sinusitis but also the development of CRSwNP and olfactory dysfunction. 13,19,20 These findings further confirmed that noninfectious inflammatory factors were involved in the occurrence and development of inflammatory diseases. Although previous studies have shown that a certain amount of G − bacteria are present in CRSwNP, the expression and distribution of LPS in CRSwNP have not been investigated.…”
Section: Introductionsupporting
confidence: 64%
“…Purified LPS is a noninfectious inflammatory factor and can regulate the release of inflammatory mediators, resulting in chronic rhinosinusitis 15 . In animal models, instilling LPS into the nasal cavity of rats or mice can induce not only acute sinusitis but also the development of CRSwNP and olfactory dysfunction 13,19,20 . These findings further confirmed that noninfectious inflammatory factors were involved in the occurrence and development of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 67%
“…55,56 In rodents, recent studies suggest that persistent nasal inflammation induces glial activation, damage of the olfactory bulb circuit, and ultimately atrophy of the olfactory bulb. 86 Of particular interest, change in olfactory bulb volume is related to change in odor threshold, which is considered to partly reflect peripheral olfactory function. Given that olfactory bulb directly receives axons from the olfactory receptor neurons, the decrease of olfactory bulb volume in CRS might be due to decreasing input from the olfactory epithelium.…”
Section: Mechanisms For Olfactory Loss In Crsmentioning
confidence: 99%
“…Reduced olfactory bulb volume has been demonstrated in CRS patients with smell loss 55,56 . In rodents, recent studies suggest that persistent nasal inflammation induces glial activation, damage of the olfactory bulb circuit, and ultimately atrophy of the olfactory bulb 86 . Of particular interest, change in olfactory bulb volume is related to change in odor threshold, which is considered to partly reflect peripheral olfactory function.…”
Section: Mechanisms For Olfactory Loss In Crsmentioning
confidence: 99%
“…The capacity for regeneration has limits and is reduced with aging or repeated insults (Child et al, 2018). Chronic nasal inflammation causes degeneration of olfactory neurons and their progenitor cells in both humans and animals (Chen et al, 2019;Hasegawa-Ishii et al, 2019). Insults that kill olfactory sensory neurons and their progenitor cells will lead to shrinkage and loss of the nasal 5 CSF outflow pathways.…”
Section: Introductionmentioning
confidence: 99%